2017
DOI: 10.1159/000480314
|View full text |Cite
|
Sign up to set email alerts
|

Snail Enhances Glycolysis in the Epithelial-Mesenchymal Transition Process by Targeting FBP1 in Gastric Cancer

Abstract: Background: Snail is a key regulator of epithelial-mesenchymal transition (EMT) in cancer. However, the regulatory role and underlying mechanisms of Snail in gastric cancer metabolism are unknown. In this study, we characterized the regulation of aerobic glycolysis by Snail in gastric cancer. Methods: The impact of Snail on glucose metabolism was studied in vitro. Combining maximum standardized uptake value (SUVmax), which was obtained preoperatively via a PET/CT scan, with immunohistochemistry staining, we fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…As anticipated, knockdown of PGK1 expression significantly upregulated epithelial marker E-cadherin and downregulated mesenchymal markers N-cadherin and vimentin. Some studies have demonstrated that glycolytic enzymes are involved in the EMT process, including FBP1 [10,11,22], PKM2 [23], and LDHA. Glycolytic enzymes are also regulated by classic EMT regulators [11,[24][25][26], so, it is not surprising that PGK1 can regulate the EMT process in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated, knockdown of PGK1 expression significantly upregulated epithelial marker E-cadherin and downregulated mesenchymal markers N-cadherin and vimentin. Some studies have demonstrated that glycolytic enzymes are involved in the EMT process, including FBP1 [10,11,22], PKM2 [23], and LDHA. Glycolytic enzymes are also regulated by classic EMT regulators [11,[24][25][26], so, it is not surprising that PGK1 can regulate the EMT process in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advancements in diagnosis and therapeutic methods, the prognosis of GC is still poor and the 5‐year survival rate for patients with GC has remained 20%‐25% . The survival of patients largely depends on the disease stage at diagnosis. The tumour–node–metastasis staging system has been widely used as an effective approach to predict the prognosis of and determine the treatment option for GC.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is named as the Warburg effect or aerobic glycolysis. The Warburg effect was considered to be at the root of carcinogenesis and progression . It not only provides cancer cells with adenosine triphosphate (ATP) and nutrients but also leads to an acidic environment that facilitates metastasis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under acidic conditions, the extracellular matrix becomes unstable, which favors the metastasis of cancer cells (32,33). For example, in gastric cancer cells, epithelial-mesenchymal-transition (EMT) regulator Snail-mediated repression of glycolytic enzyme fructose-bisphosphatase 1 (FBP1) provides metastatic advantages to gastric cancer cells (34). Some EMT regulators such as Twist1, are also HIF1α targets.…”
Section: Discussionmentioning
confidence: 99%